Determination of chloride in fresh concretes by the silver chromate method - ARAKAWA, Yutaka; HODOUCHI, Kazunori; YAMADA, Akifumi; YOSHIKUNI, Tadastugu; KATOH, Koichi (BUNSEKI KAGAKU, 1990)
Chloride in fresh concrete has been determined by using the displacement reaction with silver chlomate. Excellent results were obtained with borate buffer of pH 79. The following procedure was used. A 1 ml aliquot of the fresh concrete solution and 1 ml of 0.1 M nitric acid were placed in a 100 ml volumetric flask. Five milliliters of 0.1 M sodium borate-0.1 M nitric acid buffer solution were added and diluted to the mark with distilled water. Next, 200 mg of silver chromate (100200 mesh in size) were added to the solution and the flask was shaken for 2 min. The mixture was filtered through a No. 5C filter paper to remove any excess silver chromate and the silver chloride produced, and 1 ml of 4 M ammonia solution was added. The absorbance of filtrate was measured at 405 nm in a 1 cm cell using a chloride free blank. A linear relation was observed in the chloride concentration range of 190 mg dm-3. Thus, 3170 mM chloride in fresh concrete was determined with a relative standard deviation of 27% on repeated runs.